Pulsed electromagnetic field modulates tendon cells response in il‐1β‐conditioned environment - Vinhas, Adriana (2020)
Strategies aiming at controlling and modulating inflammatory cues may offer therapeutic solutions for improving tendon regeneration. This study aims to investigate the modulatory effect of pulsed electromagnetic field (PEMF) on the inflammatory profile of human tendonâ derived cells (hTDCs) after supplementation with interleukinâ 1Î²Â (ILâ 1Î²). ILâ 1Î²Â was used to artificially induce in-flammatory cues associated with injured tendon environments. The PEMF effect was investigated varying the frequency (5 or 17 Hz), intensity (1.5, 4, or 5 mT), and dutyâ cycle (10% or 50%) parameters to which ILâ 1Î²â treated hTDCs were exposed to. A PEMF actuation with 4 mT, 5 Hz and a 50% duty cycle decreased the production of ILâ 6 and tumor necrosis factorâ Î±Â (TNFâ Î±), as well as the expression ofÂ TNFÎ±,Â ILâ 6,Â ILâ 8,Â COXâ 2,Â MMPâ 1,Â MMPâ 2, andÂ MMPâ 3, whileÂ ILâ 4,Â ILâ 10, andÂ TIMPâ 1Â expression increased. These results suggest that PEMF stimulation can modulate hTDCs response in an inflammatory environment holding therapeutic potential for tendon regenerative strategies.